Restorative Justice Di Wilayah Hukum Polres Singkawang - Handoko, Sri; Hakim, Lukman; Sirajuddin, Sirajuddin (Legal Spirit, 2024)
A criminal act is a violation of norms regarding disruption of legal order intentionally (dolus) or unintentionally/negligently (culpa) committed by the perpetrator, where the imposition of a prison sentence on the perpetrator is necessary for the maintenance of legal order and also guaranteeing the interests of the general public. In social life, criminal acts are often found which are often resolved with restorative justice in the police. However, this settlement does not provide a deterrent to the perpetrators who end up repeating the criminal acts they previously committed or being repeated. Repetition of criminal acts as a result of resolving cases using a restorative justice approach is interesting for research, where the problem raised is what the concept of restorative justice is like and why settlements using restorative justice still provide the potential for repetition of criminal acts so that there is a need for legal construction in the future. The results of this research show that the concept of restorative justice as an alternative for resolving cases in the Police is carried out in order to realize justice, benefit and legal certainty, which is the hope of the community, so the National Police has opened up opportunities to resolve criminal cases through a restorative justice mechanism. In terms of the concept applied in the field, resolution using a restorative justice approach cannot be blamed as a reason for repeat criminal acts by the perpetrator. Because the repetition originates from the subject of the perpetrator himself.